Geometrical differences in target volumes based on 18F-fluorodeoxyglucose positron emission tomography/computed tomography and four-dimensional computed tomography maximum intensity projection images of primary thoracic esophageal cancer. Issue 8 (1st December 2014) - Guo, Y.; Li, J.; Wang, W.; Zhang, Y.; Wang, J.; Duan, Y.; Shang, D.; Fu, Z.
Summary: The objective of the study was to compare geometrical differences of target volumes based on four-dimensional computed tomography (4DCT ) maximum intensity projection (MIP ) and 18 F -fluorodeoxyglucose positron emission tomography/computed tomography ( 18 F-FDG PET /CT ) images of primary thoracic esophageal cancer for radiation treatment. Twenty-one patients with thoracic esophageal cancer sequentially underwent contrast-enhanced three-dimensional computed tomography (3DCT ), 4DCT, and 18 F-FDG PET/CT thoracic simulation scans during normal free breathing. The internal gross target volume defined as IGTVMIP was obtained by contouring on MIP images. The gross target volumes based on PET/CT images (GTVPET ) were determined with nine different standardized uptake value (SUV ) thresholds and manual contouring: SUV ≥ 2.0, 2.5, 3.0, 3.5 (SUV n ); ≥20%, 25%, 30%, 35%, 40% of the maximum (percentages of SUVmax, SUV n % ). The differences in volume ratio (VR ), conformity index (CI ), and degree of inclusion (DI ) between IGTVMIP and GTVPET were investigated. The mean centroid distance between GTVPET and IGTVMIP ranged from 4.98 mm to 6.53 mm. The VR ranged from 0.37 to 1.34, being significantly ( P < 0.05) closest to 1 at SUV 2.5 (0.94), SUV 20% (1.07), or manual contouring (1.10). The mean CI ranged from 0.34 to 0.58, being significantly closest to 1 ( P < 0.05) at SUV 2.0 (0.55), SUV 2.5 (0.56), SUV 20% (0.56), SUV 25% (0.53), or manual contouring (0.58). The mean DI of GTVPET in IGTVMIP ranged from 0.61 to 0.91, and the mean DI of IGTVMIP in GTVPET ranged from 0.34 to 0.86. The SUV threshold setting of SUV 2.5, SUV 20% or manual contouring yields the best tumor VR and CI with internal-gross target volume contoured on MIP of 4DCT dataset, but 3DPET/CT and 4DCT MIP could not replace each other for motion encompassing target volume delineation for radiation treatment.